Age-dependent changes in 8-oxoguanine-DNA glycosylase activity are modulated by adaptive responses to physical exercise in human skeletal muscle. - Radak, Zsolt; Bori, Zoltan; Koltai, Erika; Fatouros, Ioannis G; Jamurtas, Athanasios Z; Douroudos, Ioannis I; Terzis, Gerasimos; Nikolaidis, Michalis G; Chatzinikolaou, Athanasios; Sovatzidis, Apostolos; Kumagai, Shuzo; Naito, Hisahi; et al. (Free Radic Biol Med, 2011)
8-Oxo-7,8-dihydroguanine (8-oxoG) accumulates in the genome over time and is believed to contribute to the development of aging characteristics of skeletal muscle and various aging-related diseases. Here, we show a significantly increased level of intrahelical 8-oxoG and 8-oxoguanine-DNA glycosylase (OGG1) expression in aged human skeletal muscle compared to that of young individuals. In response to exercise, the 8-oxoG level was lastingly elevated in sedentary young and old subjects, but returned rapidly to preexercise levels in the DNA of physically active individuals independent of age. 8-OxoG levels in DNA were inversely correlated with the abundance of acetylated OGG1 (Ac-OGG1), but not with total OGG1, apurinic/apyrimidinic endonuclease 1 (APE1), or Ac-APE1. The actual Ac-OGG1 level was linked to exercise-induced oxidative stress, as shown by changes in lipid peroxide levels and expression of Cu,Zn-SOD, Mn-SOD, and SIRT3, as well as the balance between acetyltransferase p300/CBP and deacetylase SIRT1, but not SIRT6 expression. Together these data suggest that that acetylated form of OGG1, and not OGG1 itself, correlates inversely with the 8-oxoG level in the DNA of human skeletal muscle, and the Ac-OGG1 level is dependent on adaptive cellular responses to physical activity, but is age independent.
Keywords: Adult; Age Factors; Aged; Base Sequence; DNA Glycosylases; DNA Primers; Exercise; Guanine; Humans; Middle Aged; Muscle, Skeletal; Reverse Transcriptase Polymerase Chain Reaction